Differentiated Customers’ Loyalty Development in Relation to Different Customer Lifetime Values - Loštakova, Hana; Kohoutová, Martina; Koblížková, Andrea (Ekonomika, 2004)
This paper shows that it is not effective to increase the total market share at present, but it is more effective to pay attention to increasing the share at key customers (wallet share). Building a differentiated customer relationship management and a customers’ loyalty according to different customer lifetime value (CLTV) is a must. This paper presents the results of a qualitative marketing research by means of the method of individual interviews with SBU managers, marketing managers and sales managers in the Czech industrial firms operating on B-to-B markets. This research was focused on the benefits of customers’ loyalty development and on mapping the customers’ loyalty development instruments available for building long-term relationships with key customers in the contemporary turbulent market environment.